Multi-agent systems : 16th European Conference, EUMAS 2018, Bergen, Norway, December 6-7, 2018, Revised selected papers /: 16th European Conference, EUMAS 2018, Bergen, Norway, December 6-7, 2018, Revised selected papers. (2019) - Unknown
No abstract available